2014
DOI: 10.1371/journal.pone.0091418
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of De Novo Unique Differentially Expressed Genes Related to Evolution in Exercise Response during Domestication in Thoroughbred Race Horses

Abstract: Previous studies of horse RNA-seq were performed by mapping sequence reads to the reference genome during transcriptome analysis. However in this study, we focused on two main ideas. First, differentially expressed genes (DEGs) were identified by de novo–based analysis (DBA) in RNA-seq data from six Thoroughbreds before and after exercise, here-after referred to as “de novo unique differentially expressed genes” (DUDEG). Second, by integrating both conventional DEGs and genes identified as being selected for d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 64 publications
(76 reference statements)
1
18
0
Order By: Relevance
“…Investigators have used RNA‐Seq to characterize the expression profile of genes critical to the differentiation and regulation of cells during embryogenesis,90 and to characterize the expression and inferred function of RNAs in the equine sperm transcriptome 89. Several studies also have used RNA‐Seq in horses to identify differentially expressed genes when comparing blood, muscle (obtained by biopsy), or both before and after exercise or racing 86, 87, 92. These studies have successfully identified pathways involved in stress during and while recovering from exercise.…”
Section: Next Generation Sequencing Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigators have used RNA‐Seq to characterize the expression profile of genes critical to the differentiation and regulation of cells during embryogenesis,90 and to characterize the expression and inferred function of RNAs in the equine sperm transcriptome 89. Several studies also have used RNA‐Seq in horses to identify differentially expressed genes when comparing blood, muscle (obtained by biopsy), or both before and after exercise or racing 86, 87, 92. These studies have successfully identified pathways involved in stress during and while recovering from exercise.…”
Section: Next Generation Sequencing Techniquesmentioning
confidence: 99%
“…Several studies have reported the application of RNA-Seq in horses in an attempt to identify differentially expressed genes. [86][87][88][89][90][91][92][93][94][95] To the authors' knowledge, the first report of RNA-Seq in horses was an effort to characterize the transcriptome and tissue-specific expression profiles from 8 equine tissues. 94 A subsequent study focused on characterizing gene expression by RNA-Seq in immunologically active tissues.…”
Section: Next Generation Sequencing Techniquesmentioning
confidence: 99%
“…A widely used systems biology technique to highlight biological processes is gene category over-representation analysis (Park et al, 2014). To perform this analysis genes are grouped into categories by a common biological property and then tested to find categories that are over-represented.…”
Section: 4mentioning
confidence: 99%
“…2B). There are many tools available for de novo transcriptome assembly and differential expression analysis of these transcriptomes (Davidson, Oshlack, 2014;Grabherr et al, 2011;Haas et al, 2013;Robertson et al, 2010;Schulz et al, 2012) In cases where the reference genome is of low quality, i.e., with misassemblies and large genomic deletions, genes of interest that are absent in the genome assembly can be present in the transcriptome (Park et al, 2014). Another possible approach is mapping assembled transcriptomes to a closely related reference genome, which has been utilized with non-human primates, across the mammalian clade, and the zebra finch and human genomes (Fig.…”
Section: Genome Vs Transcriptome Based Expression Studies In Reptilesmentioning
confidence: 99%